SYMBIOCLADIUS RHITHROGENAE (ZAVREL, 1924) (DIPTERA: CHIRONOMIDAE): A NEW FINDING FOR THE ENTOMOFAUNA OF SERBIA (Acta Entomologica Serbica, 2023)
During hydrobiological research on the territory of Serbia in 2011 and 2012, the species Symbiocladius rhithrogenae (Zavrel, 1924) (Diptera: Chironomidae) was found in the Rača stream at three localities. Our study is the first record of this parasite in Serbia. The parasite only infected the larvae of Rhithrogena cf. semicolorata (Ephemeroptera: Heptageniidae) and was not found in any other species from the family Heptageniidae. This study contributes to the knowledge about the diversity of the family Chironomidae in Serbia.